2001
DOI: 10.1039/b105849p
|View full text |Cite
|
Sign up to set email alerts
|

Aluminium uptake and excretion in potroom workers of a new primary aluminium smelter during the construction stagePresented at ENVIROMIN 2001 at Skukuza, Kruger National Park, South Africa, 14–18 July, 2001.

Abstract: The aim of this study was to define bio-accumulation and excretion patterns of aluminium in newly employed potroom workers as well as changes in ambient aluminium levels in the potrooms of a modern aluminium smelter during the plant construction stage and one year into full production. A study was carried out on 115 newly employed volunteer potroom workers at various intervals, over a total period of 36 months. Before commencement of employment a structured questionnaire was completed by all study participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…These observations, at least in part, may be related to the different rates of metal elimination in man. Al [Rollin et al, 2001], Cd [Lauwerys et al, 1994], Co [Mosconi et al, 1994], Cr [Petersen et al, 2000], and Pb [Hryhorczuk et al, 1985] are slowly eliminated from blood. In contrast, Mn [Lu et al, 2005], Ni [Patriarca and Lyon, 1997] and Zn [McLean and Speakman Jr, 1995] are eliminated more rapidly.…”
Section: Discussionmentioning
confidence: 99%
“…These observations, at least in part, may be related to the different rates of metal elimination in man. Al [Rollin et al, 2001], Cd [Lauwerys et al, 1994], Co [Mosconi et al, 1994], Cr [Petersen et al, 2000], and Pb [Hryhorczuk et al, 1985] are slowly eliminated from blood. In contrast, Mn [Lu et al, 2005], Ni [Patriarca and Lyon, 1997] and Zn [McLean and Speakman Jr, 1995] are eliminated more rapidly.…”
Section: Discussionmentioning
confidence: 99%
“…The relative contribution of biological and behavioural factors to the long-term stability is unclear. Slow biological processes of Al uptake and elimination are certainly involved (Letzel et al 1999;Röllin et al 2001;Sjögren et al 1988). However, to what degree biological features of the workers (accumulation, elimination), individual behaviour when welding (breath protection), or job differences contribute to the stable interindividual differences cannot be answered.…”
Section: Al-biomonitoring Featuresmentioning
confidence: 98%
“…Clearly, in the T-study with higher exposure all biomonitoring measures showed stronger long-term stability over the 4 years, corresponding to the assumption of slow biological processes of Al uptake and elimination (Letzel et al 1999;Röllin et al 2001;Sjögren et al 1988).…”
Section: Al-biomonitoring Featuresmentioning
confidence: 97%